2016
DOI: 10.3390/met6080191
|View full text |Cite
|
Sign up to set email alerts
|

Serration Behavior in Pd77.5Cu6Si16.5 Alloy

Abstract: Abstract:The strain-rate-dependent plasticity under uniaxial compression at the strain rates of 2 × 10 −3 , 2 × 10 −4 and 2 × 10 −5 s −1 in a Pd 77.5 Cu 6 Si 16.5 alloy is investigated. At different strain rates, the serration events exhibit different amplitudes and time scales. The intersection effects take place obviously, and the loading time is much longer than the relaxation time in the serration event at three strain rates. However, the time intervals between two neighboring serrations lack any time scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…This phenomenon is known as the Portevin-Le Chatelier (PLC) effect and depends on the strain rate and temperature [9]. This serration phenomenon has been reported for various metallic materials besides aluminum alloys [10][11][12][13]. When serration occurs, a pattern may be formed on the material surface.…”
Section: Introductionmentioning
confidence: 94%
“…This phenomenon is known as the Portevin-Le Chatelier (PLC) effect and depends on the strain rate and temperature [9]. This serration phenomenon has been reported for various metallic materials besides aluminum alloys [10][11][12][13]. When serration occurs, a pattern may be formed on the material surface.…”
Section: Introductionmentioning
confidence: 94%
“…Wu et al [17] ) exhibit lower penetration depth, higher elastic recovery, and lower wear volume than the substrate, indicating the excellent wear resistance of the coatings, due to the high hardness and high hardness/elastic modulus ratio. Zhong et al [18] studied the serrated-flow behavior of a multicomponent amorphous Pd 77.5 Cu 6 Si 16.5 alloy under uniaxial compression at the strain rates 2 × 10 −3 , 2 × 10 −4 and 2 × 10 −5 s −1 . They observed that the elastic energy density displays a power-law distribution at the strain rate of 2 × 10 −3 and concluded that the self-organized critical behavior emerges with increasing strain rates.…”
Section: Contributionsmentioning
confidence: 99%